Xanthine oxidase inhibitory activity of compounds from Chythrantus claneianus - Gojayev, Anar Sahib; Bankeu, Jean Jules Kezetas; Awantu, Angelbert Fusi; Nkanwen, Eric René Sieliatchom; Ali, Muhammad Shaiq; Lenta, Bruno Ndjakou; Guliyev, Akif Alakbar; Noungoué, Didérot Tchamo; Ngouela, Silvère Augustin; Tsamo, Etienne (Bangladesh Journal of Pharmacology, 2013)
Phytochemical investigation of the stem bark and the trunk of Chythrantus claneianus led to the isolation of six known compounds named β-sitosterol (1), umbelliferone (2), scopoletin (3), benjaminamide (4), β-sitosterol-3-O-β-D-glucopyranoside (5) and panconoside B (6). All these compounds were isolated for the first time from this plant species. The chemical structures of isolates were elucidated on the basis of 1 and 2 D-NMR spectra and other spectroscopic techniques including UV–vis, FT-IR, HR-ESIMS and HR-FABMS. The isolates were tested in vitro for their inhibitory properties towards xanthine oxidase enzyme. Compounds 2, 3 and 6 showed weak inhibitory activities on the enzyme with IC50 values ranging from 307 µM for compound 6 to 475 µM for compound 3, while the extract and compounds 1, 4 and 5 showed extremely weak activities with inhibition percentage less than 50%.